“DARI LUCU MENUJU KOMERSIAL” SEBUAH TINJAUAN SEMIOTIKA VISUAL KOMIK IKLAN TAHI LALATS - Hendrawan, Faldi (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2023)
The Tahilalats advertising comics are a differentiator from works that only aim to convey humorous messages on Instagram. An overview of advertising comics with commercial purposes is interesting because the contents of commercial advertisements for a product become a new pattern of creativity for Tahilalats creators. The object of the problem taken from the work entitled “Surprise” offers a form of negotiation between the aim of being funny and commercial advertising The Ponds Men advertisement is a promotional idea for men’s skin care products which is humorously visualized in ten comic strip panels. The series of panels is a sign structure that will be dissected in order to find the right meaning to show the persuasion message of a commercial product. The accuracy of meaning can be seen from the visualization of the text or aspects of form and context or content as part of the marking system. The marking system will be reviewed based on the sign structure of Barthes’s semiotic theory, namely lexia. The meaning analysis begins by re-reading the nine comic panels into four lexias by naming them based on the logic of meaning, not chronology. In the lexia you will find code categories used as sign dynamic rules according to Barthes based on the perception and culture of the users as interpreters including hermeneutic codes, semimic or semantic codes, symbolic codes, proairetic or action codes, and cultural codes. The code becomes the main reference showing the context in the form of a persuasive message from a Ponds Men commercial advertisement. The context of being funny can be visualized with aspects of character shape, cartoon-style expressions that are simple and simple. The supporting theory is in the form of relays and intertextuality from Julia Kristeva to review the performance of the tagging system based on caption text in the form of titles and descriptions in the Instagram Tahilalats column. In this case, it can show that the commercial message of Ponds Men’s products can be combined appropriately according to Tahilalats’ cute characterization.Keyword: advertising, comic, tahilalats, visual semiotics